ANALYSIS OF THE CO-MANAGING PROCESS IN THE MANAGEMENT OF THE MANGROVE BOTANICAL GARDENS CONSERVATION AREA IN SURABAYA CITY - Naba Arum Kinasih; Bagus Nuari Harmawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Global environmental issues are inseparable from mangrove deforestation. Mangrove areas continue to decline every year, while mangrove ecosystems are the most efficient carbon capture and storage systems in the world, currently storing carbon equivalent to more than 21 billion tons of CO2. Mangroves protect communities from the impacts of climate change and generate income through ecotourism and their products. Therefore, their preservation needs to be a focus of the government and the entire community, and efforts must be made to conserve these areas. Kebun Raya Mangrove (KRM) is a mangrove conservation area in the center of Surabaya. This study uses a descriptive qualitative approach. This study aims to identify, analyze, and describe the management of the Kebun Raya Mangrove Kota Surabaya so that it can be used as updated information and enrich studies related to the importance of conservation areas. The results of the study show the roles of several actors, including the Dinas Ketahanan Pangan dan Pertanian Kota Surabaya, NGOs, and the community.